2019
DOI: 10.1016/j.joca.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

TFEB protects nucleus pulposus cells against apoptosis and senescence via restoring autophagic flux

Abstract: s u m m a r yObjective: Excessive apoptosis and senescence of nucleus pulposus (NP) cells are major pathological changes in intervertebral disc degeneration (IVDD) development; previous studies demonstrated pharmacologically or genetically stimulation of autophagy may inhibit apoptosis and senescence in NP cells. Transcription factor EB (TFEB) is a master regulator of autophagic flux via initiating autophagy-related genes and lysosomal biogenesis. This study was performed to confirm whether TFEB was involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…Regrettably, there have been no additional studies to discuss the effect of TGF-b on the necroptosis of IVD cells. Growing evidences demonstrate that cellular senescence is one of the major contributors to IVD degeneration 89 , and TGF-b signaling can regulate cellular senescence in many other cell types 90,91 . However, the effect of TGF-b signaling on the regulation of cellular senescence in IVD is still unclear, and further studies are needed.…”
Section: Promotion Of Cell Proliferation and Inhibition Of Cell Deathmentioning
confidence: 99%
“…Regrettably, there have been no additional studies to discuss the effect of TGF-b on the necroptosis of IVD cells. Growing evidences demonstrate that cellular senescence is one of the major contributors to IVD degeneration 89 , and TGF-b signaling can regulate cellular senescence in many other cell types 90,91 . However, the effect of TGF-b signaling on the regulation of cellular senescence in IVD is still unclear, and further studies are needed.…”
Section: Promotion Of Cell Proliferation and Inhibition Of Cell Deathmentioning
confidence: 99%
“…Notably, Xu et al found that treatment of rat NP cells with rapamycin (Rap), a classical autophagy activator, can potently prevent ECM degradation induced by inflammatory factors such as tumor necrosis factor-α and interleukin-1β [17]. Recently, autophagic flux was also reported to be markedly impaired in rat NP cells under oxidative stress [18]. Therefore, autophagy upregulation coupled with autophagic flux enhancement might represent a promising therapeutic strategy for IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical trials using BMSCs for the treatment of chronic low back pain caused by IVD degeneration have been conducted, and long-term results indicate that injection of BMSCs into IVDs is well tolerated and provides substantial improvement in pain and function 2 . Furthermore, recent studies confirmed that NPCs can be protected from apoptosis through induction of autophagy during the process of IVD degeneration 11,54,55 . In the compression-induced model, BMSCs could inhibit the mitochondrial pathway to protect NPCs from apoptosis 39 .…”
Section: Discussionmentioning
confidence: 91%